STUDI PENGARUH PENAMBAHAN SABUT KELAPA PADA PEMBUATAN PUPUK CAIR DARI LIMBAH AIR CUCIAN IKAN TERHADAP KUALITAS UNSUR HARA MAKRO (CNPK) - Anik Waryanti; Sudarno Sudarno; Endro Sutrisno (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
The processing of fish, would produce fluid that comes from the process of cutting, washing and processing of products. Fisheries waste, especially wastewater, is usually discharged directly into the environment and caused environmental nuisance. Fishing industry wastewater contains a lot of protein and fat, resulting in nitrate and ammonia values were quite high, so it can be used as raw material for a complete organic fertilizer. In this study, the wastewater derived from cleaning fishes is used as the raw material for liquid fertilizer because its nutrient content is very potentially to be used as a liquid fertilizer. One way to make liquid fertilizer is through fermentation techniques. In this case, it used six (6) variations in the addition of coconut fiber to determine the effect of macro nutrients for making the best liquid fertilizer. The variations were: 0 ml, 100 ml, 200 ml, 300 ml, 400 ml, 500 ml and it was being fermented for 28 days. The amount of coconut fiber that produces the best liquid fertilizer is by adding 100 ml of it which resulting in nutrient macro content of C-organic, nitrogen, phosphorus and potassium, respectively 11.69%, 2.251%, 0.74% and 0.029% at 14th day and the content of macro nutrients on 28th day for C-organic, Nitrogen, Phosphorus and Potassium are respectively 11.28%, 2.366%, 0.77% and 0.041%.